2017
DOI: 10.5964/ejop.v13i4.1198
|View full text |Cite
|
Sign up to set email alerts
|

The Sensation Seeking Scale (SSS-V) and its use in Latin American adolescents: Alcohol consumption pattern as an external criterion for its validation

Abstract: Sensation Seeking is a trait defined by the seeking of varied, novel, complex, and intense situations and experiences, and the willingness to take physical, social, and financial risks for the sake of such experience. The Sensation Seeking Scale (SSS-V) is the most widely used measure to assess this construct. In previous studies a variety of psychometric limitations were found when using the SSS-V with Latin American population. The purpose of this study is to present additional psychometric properties for it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
1
4
0
9
Order By: Relevance
“…A variety of studies (Hittner & Swickert, 2006;Legrand, Kaltenbach, Joly, et al, 2007;Yanovitzky, 2006;Zuckerman, 1994Zuckerman, , 2007 argue that high levels of sensation seeking correlate positively with alcohol consumption and recently (Smorti & Guarnieri, 2013) positive correlations have been found between the intensity scale and alcohol consumption, as well as between the novelty scale and the amount of alcohol consumed. Research in Latin America (González-Iglesias, Gómez-Fraguela, Gras, & Planes, 2014;Palacios & Cañas, 2010;Romero Saletti, Olivo Chang, Pérez-Aranibar, & Otiniano Campos, 2017;Schmidt, Molina, & Raimundi, 2017) has found that sensation seeking scores tend to be greater among those who consume alcohol, which confirms the importance of the search for sensations in explaining alcohol consumption in young people.…”
Section: Introductionmentioning
confidence: 91%
“…A variety of studies (Hittner & Swickert, 2006;Legrand, Kaltenbach, Joly, et al, 2007;Yanovitzky, 2006;Zuckerman, 1994Zuckerman, , 2007 argue that high levels of sensation seeking correlate positively with alcohol consumption and recently (Smorti & Guarnieri, 2013) positive correlations have been found between the intensity scale and alcohol consumption, as well as between the novelty scale and the amount of alcohol consumed. Research in Latin America (González-Iglesias, Gómez-Fraguela, Gras, & Planes, 2014;Palacios & Cañas, 2010;Romero Saletti, Olivo Chang, Pérez-Aranibar, & Otiniano Campos, 2017;Schmidt, Molina, & Raimundi, 2017) has found that sensation seeking scores tend to be greater among those who consume alcohol, which confirms the importance of the search for sensations in explaining alcohol consumption in young people.…”
Section: Introductionmentioning
confidence: 91%
“…Las bases biológicas, incluidas las genéticas del rasgo de BS son notables (Aluja et al, 2019;Oberlin et al, 2019), aunque también muestra sensibilidad al ambiente (Stoel, De Geus & Boomsma, 2006). Asimismo, se asocia con conducción temeraria (Qu, Zhang & Ge, 2020), consumo de sustancias (Chen et al, 2013;Jamt et al, 2020;Lydon-Staley, Falk, & Bassett, 2019;Merchán-Clavellino et al, 2020;Schmidt, Molina & Raimundi, 2017), conductas sexuales de riesgo (Chen et al, 2013;Dunne et al, 2019;Longo et al, 2020) aunque en otros estudios no se observa dicha asociación (Espinoza et al, 2019). También se ha estudiado la relación con conductas de riesgo de forma genérica (Lydon-Staley, Falk, & Bassett, 2019;Safa et al, 2019).…”
Section: Estudio Psicométrico En Población Adolescente Mexicanaunclassified
“…Según varios autores (Escorial, 2017;Manna, Faraci & Como, 2013;Palacios-Delgado, 2015;Romero-Saletti, et al, 2017;Schmidt, Molina & Raimundi, 2017) el instrumento más utilizado para evaluar el comportamiento de búsqueda de experiencias nuevas, que identifica un alto nivel de arousal y que se relacionan con conductas riesgosas, es la Escala Búsqueda de Sensaciones -Forma V (SSS-V, por sus siglas en inglés), elaborada por Zuckerman, et al (1978). La SSS-V fue diseñada para evaluar 4 dimensiones mediante 40 ítems con respuestas dicotómicas si/no; las dimensiones que evalúa son: Búsqueda de Aventura y Emoción (BAE), Búsqueda de Experiencia (BE), Desinhibición (DES) y Susceptibilidad al Aburrimiento (SAB).…”
Section: Método Tipo De Estudiounclassified
“…The behavior of seeking experience includes expectations and needs related to activities bringing new experiences that visitors have never had before, such as living in a different style and making new friends (Schmidt et al, 2017). Another study by Smock and Holt (1962) emphasized that experience is the feeling caused by the difference between what one expects and the true experience of the trip.…”
Section: Experience Seekingmentioning
confidence: 99%